pH variation in medical implant biofilms: Causes, measurements, and its implications for antibiotic resistance - Behbahani, Shayesteh Beladi; Kiridena, Sachindra D.; Wijayaratna, Uthpala N.; Taylor, Cedric; Anker, Jeffrey N.; Tzeng, Tzuen-Rong Jeremy (Frontiers in Microbiology, 2022)
The advent of implanted medical devices has greatly improved the quality of life and increased longevity. However, infection remains a significant risk because bacteria can colonize device surfaces and form biofilms that are resistant to antibiotics and the host’s immune system. Several factors contribute to this resistance, including heterogeneous biochemical and pH microenvironments that can affect bacterial growth and interfere with antibiotic biochemistry; dormant regions in the biofilm with low oxygen, pH, and metabolites; slow bacterial growth and division; and poor antibody penetration through the biofilm, which may also be regions with poor acid product clearance. Measuring pH in biofilms is thus key to understanding their biochemistry and offers potential routes to detect and treat latent infections. This review covers the causes of biofilm pH changes and simulations, general findings of metabolite-dependent pH gradients, methods for measuring pH in biofilms, effects of pH on biofilms, and pH-targeted antimicrobial-based approaches.